Molecular hierarchical release using hydrogenated graphene origami under electric field - Adesola Ademiloye (Materials Science in Semiconductor Processing, 2021)
In recent years, drug delivery has progressively become one of the main research areas in the field of biomedicine. However, the graded drug release remains a serious challenge at the nano-scales. Herein, we successfully simulated the graded release of C60 and C180 from the graphene box inspired by the origami technique under the control of an external electric field via molecular dynamics (MD) simulations. Our results provide a feasible scheme for hierarchical drug delivery at the nano-scales. The graphene origami was generated through the folding of graphene guided by its creases which were created by combining carbon atoms with hydrogen atoms and transforming sp2 to sp3 bonds at the combination line. We can construct complex graphene origami by designing reasonable hydrogen atoms distribution on graphene. This provides a simple and practicable program for designing complex graphene-based nanodevices for drug delivery.